NONVERBAL COMMUNICATION BETWEEN TEACHERS AND STUDENTS WITH DISABILITIES IN BUILDING EFFECTIVE COMMUNICATION AT A STATE SPECIAL SCHOOL (SLB) - Br Manik, Nurhalimah; Sahputra, Dika (TASAMUH, 2024)
This study aims to determine the nonverbal communication of teachers and students with disabilities in building effective communication in SLB Negeri. This study uses descriptive qualitative research. Data collection techniques include observation, interviews, and documentation. Informants in this study were two teachers, the main informants, and the principal, the supporting informant. Data analysis techniques include data reduction, data presentation, and conclusion. This research uses a triangulation data validity test. The results of this study indicate that teachers and students with disabilities use nonverbal communication, namely sign language, kinesics, and lip reading. Communication between teachers and students with disabilities in SLB Negeri is very effective because it addresses several important aspects. Teachers build the principle of mutual respect, always provide support and show Empathy, speak in good sentences and not in a hurry, and convey material clearly and accurately to avoid multiple interpretations. In addition, teachers should show a humble attitude by accepting each student's strengths and weaknesses. These aspects make communication between teachers and students with disabilities in SLB Negeri effective and meaningful.